2009
DOI: 10.1016/j.pain.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of exposure and acceptance strategies to improve functioning and quality of life in longstanding pediatric pain – A randomized controlled trial

Abstract: Although several studies have illustrated the effectiveness of cognitive behavior therapy (CBT) on adult pain patients, there are few randomized controlled trials on children and adolescents. There is particularly a need for studies on pediatric patients who are severely disabled by longstanding pain syndromes. Acceptance and Commitment Therapy, as an extension of traditional CBT, focuses on improving functioning and quality of life by increasing the patient's ability to act effectively in concordance with per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
303
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(332 citation statements)
references
References 64 publications
23
303
1
5
Order By: Relevance
“…This is in keeping with the findings of other studies that reported treatment gains to be more evident a few months post treatment [21][22][23]. Although the proportion of participants diagnosis free at 2YFU was not statistically different, a larger sample size may have increased the power to detect significant findings, as there was a trend towards a greater proportion of CBT participants being diagnosis free.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is in keeping with the findings of other studies that reported treatment gains to be more evident a few months post treatment [21][22][23]. Although the proportion of participants diagnosis free at 2YFU was not statistically different, a larger sample size may have increased the power to detect significant findings, as there was a trend towards a greater proportion of CBT participants being diagnosis free.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have shown maintenance of gains one year post treatment [15][16][17]; and including youth 2-3 years [3], 3.5 years [18], 6 years [19] and 7.4 years [20] following treatment cessation. Assessing outcomes over the long term may be particularly indicated among children treated with ACT as studies of ACT for children with a spectrum of presenting problems have found that treatment gains were either not fully evident at posttreatment (or initial follow-up), or that greater improvements for ACT were obtained some months after therapy cessation [21][22][23]. This underscores the need for the inclusion of longer follow-up time points in research.…”
Section: Introductionmentioning
confidence: 99%
“…There are now six published RCTs of ACT related to chronic pain in adults, 7,14,75,88,90,91, and one in young people. 92 There are other trials that are pseudo-randomized, partly controlled, or pilot studies, 36,58,87 a partial reanalysis of treatment outcome focused on older adults, 54 and several larger scale effectiveness studies, 52,84 including a large treatment cohort that showed good outcomes at three years post treatment. 86 There are also two small RCTs of ACT for headache.…”
Section: Psychological Flexibility Clarifies and Empowers Other Existmentioning
confidence: 99%
“…The results of the study of Veehof et al (2011) suggest that ACT interventions improve health and reduce mental pressures by changing psychological flexibility and paying conscious attention to the symptoms of anxiety [29]. Wicksell et al (2009) reported that flexibility throughout the interventions reduces symptoms of depression and anxiety [31]. Moreover, this study shows that ACT affects anxiety-related disorders [15,16].…”
Section: Discussionmentioning
confidence: 71%